2014
DOI: 10.1021/ic5013457
|View full text |Cite
|
Sign up to set email alerts
|

High-Valent Chromium–Oxo Complex Acting as an Efficient Catalyst Precursor for Selective Two-Electron Reduction of Dioxygen by a Ferrocene Derivative

Abstract: Efficient catalytic two-electron reduction of dioxygen (O2) by octamethylferrocene (Me8Fc) produced hydrogen peroxide (H2O2) using a high-valent chromium(V)-oxo corrole complex, [(tpfc)Cr(V)(O)] (tpfc = tris(pentafluorophenyl)corrole) as a catalyst precursor in the presence of trifluoroacetic acid (TFA) in acetonitrile (MeCN). The facile two-electron reduction of [(tpfc)Cr(V)(O)] by 2 equiv of Me8Fc in the presence of excess TFA produced the corresponding chromium(III) corrole [(tpfc)Cr(III)(OH2)] via fast ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 99 publications
1
36
0
Order By: Relevance
“…Unlike Fe complexes, Co complexes in general catalyze the 2e reduction of O 2 because the peroxo intermediates of Co are challenging to undergo heterolytic O-O bond cleavage to generate terminal Co-oxo species that have large d electron counts and thus are high in energy. [35][36][37] Several molecular design strategies have been reported to improve the selectivity for the 4e ORR, including (1) formation of intramolecular hydrogen bonding interactions to stabilize O 2 adducts, 27,30,38,39 (2) appending acid groups to assist proton delivery, 19,28,29,40 and (3) introduction of functional groups to ensure rapid electron transfer between catalyst molecules and electrodes. 34,[41][42][43][44] Additionally, for complexes of late-transition metals, such as Co, it is found that dinuclear complexes are typically more efficient than mononuclear analogues to catalyze the 4e reduction of O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike Fe complexes, Co complexes in general catalyze the 2e reduction of O 2 because the peroxo intermediates of Co are challenging to undergo heterolytic O-O bond cleavage to generate terminal Co-oxo species that have large d electron counts and thus are high in energy. [35][36][37] Several molecular design strategies have been reported to improve the selectivity for the 4e ORR, including (1) formation of intramolecular hydrogen bonding interactions to stabilize O 2 adducts, 27,30,38,39 (2) appending acid groups to assist proton delivery, 19,28,29,40 and (3) introduction of functional groups to ensure rapid electron transfer between catalyst molecules and electrodes. 34,[41][42][43][44] Additionally, for complexes of late-transition metals, such as Co, it is found that dinuclear complexes are typically more efficient than mononuclear analogues to catalyze the 4e reduction of O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…16 −25 In the specific case of catalytic O 2 reduction, investigations in solution are essential to obtain insights into the factors that control the competition between four-and two-electron reduction processes. 19,26,27 The reactivity of metal complexes with O 2 is mainly regulated by the nature of the transition metal ion, by the donor atom set supplied by the supporting ligand, and finally by second coordination sphere effects. Among transition metals, manganese exhibits extremely rich oxygen chemistry in both biological and synthetic systems.…”
Section: Introductionmentioning
confidence: 99%
“…7−10 Other electron source materials such as ferrocene and cobaltocene are also known. 11,12 For the quantitative analysis of O 2 activation, electrochemical methods were employed. 13−15 Although the addition of reductants was successfully applied to investigate the course of biomimetic O 2 activation, it is difficult to employ this method in catalytic oxygenation reactions because of the cost of these reductants as compared with usual oxidants like hydrogen peroxide.…”
Section: ■ Introductionmentioning
confidence: 99%